Pengaruh Laba dan Arus Kas Terhadap Kondisi Financial Distress (Studi Pada Perusahaan Pertambangan Batu Bara Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Afdholul Laily; Afi Rahmat Slamet; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study is to find out how the influence of Profit and Cash Flow on the Financial Distress condition of Coal Mining Companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. The independent variables in this study are Profit and Cash Flow, while the other variables in this study are Financial Distress. The population in this study are coal mining companies listed on the Indonesia Stock Exchange in the 2017-2019 period with a total of 23 companies. The sample of this study was taken using a purpose sampling technique, which is to determine the sample based on certain criteria so that a total sample of 20 companies is obtained. The data collection method used is the documentation method, namely by documenting data originating from the annual report downloaded from the IDX web. The analysis technique in this research is by using multiple linear regression analysis. From the results of Key data analysis that Profit and Cash Flow have a simultaneous effect on Financial Distress, Profit and Cash Flow have a partial effect on Financial Distress. Keywords: Profit, Cash Flow, Financial Distress.